The end game - Coulter, Catherine; Ellison, J. T. (New York : G. P. Putnam's Sons, an imprint of Penguin Random House LLC, 2015)
A bomb-making expert, Vanessa joins forces with FBI agent Nicholas Drummond and Mike Caine to stop a devious plan to assassinate the President.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Terrorism -- Prevention -- Fiction; Intelligence officers -- Fiction; Suspense fiction; Mystery fiction; Detective and mystery stories